Codification of medical legislation from the position of doctors' legal culture improvement in Ukraine. - Tsekhmister Yaroslav; Lysenko Oleksandra (Borys Grinchenko Kyiv Metropolitan University, 2018)
The article, being offered, emphasizes the modern conditions of legislation in Ukraine on issues of health care. Presents the doctors survey results about level of their knowledge in the sphere of medical law. 610 respondents from 9 regions of Ukraine took part in the survey. The survey results indicate insufficient of doctors knowledge's in the sphere of medical law at all stages of vocational training. Were identified difficulties in working with normative legal acts regulating medical practice, in particular due to their number and lack of systematization. Also, it was found that 100% of respondents would like to attend a medical law course, and examine the rights and responsibilities of health professionals, the legal protection of doctors, the legal aspects of the interaction between physicians and patients, health legislation, patients' rights and responsibilities. Was made the analysis of legal relations between entities in the sphere of health care as to issues, related to indemnification of harm, caused by handicap, other health injury or death of natural person in terms of Civil Code of Ukraine and practice of civil law proceeding. Article justifies the expediency of creating the Medical Code of Ukraine, that will systematize of national legislation in the sphere of health care through its codification and establishment of basic document - Medical Code of Ukraine - will assist to improvement in level of legal culture at doctors, improvement in their positive responsibility, consolidation of moral ethical values and high professional landmarks among medical men that will assist to improvement in quality of rendering the medical aid to population for reinforcement and preservation of the highest social value - human life and health.